THE TEACHER'S GUIDANCE AND COUNSELLING EFFORTS IN IMPROVING STUDENT UNDERSTANDING ABOUT THE DANGERS OF SMOKING IN SENIOR HIGH SCHOOL 6 PADANGSIDIMPUAN ACADEMIC YEAR 2015-2016 - Nurhasanah Pardede (Universitas Muhammadiyah Tapanuli Selatan, 2016)
This research is based upon the student's understanding of the problems still low about the dangers of smoking. As for the goal to be achieved is to know the teacher's guidance and counselling efforts in improving student understanding about the dangers of smoking in SMA Negeri 6 Padangsidimpuan academic year 2015-2016 located on JL. Sutan Soripada Noble No. 25 a. Teacher guidance and counselling is an informant in this research. On the research of this kind of research used the qualitative case study method. Qualitative research i.e. research methods were used to examine the conditions of natural objects, where the researcher as a key instrument. Engineering data collection done in triangulation (combined) that is doing the observation (observation), interview (interview), the study of documentation and a combination of the three. Based on the results of interviews with informants researchers HS (BK teacher), the efforts of teacher guidance and counselling in improving student understanding about the dangers of smoking in this school is by granting the existing services in the guidance and counselling as well as supporting activities. Furthermore, efforts are being made to reduce the problem of students who smoke in the school environment this is the strict sanctions, the granting of services on the issue of smoking. But even though the school has given strict sanctions in cooperation between teachers BK with parents is very important to help alleviate this problem. Because without the support of parents the school will not get over it in full this time because the students more in the family environment. BK teacher has made the program planning, organizing, implementing, monitoring and assesment in student improve understanding about the dangers of smoking. In this case we as teachers BK has made the annual program planning, semiannual, monthly, weekly up to daily. As for the results of our efforts as a teacher in improving students ' understanding of BK on the danger of smoking was already beginning to look in stages where it can be known once given services, guidance and direction from the teacher area students problem BK has begun to wane. Probably because our teacher BK already gives a description of smoking, and the dangers therein.